Wołanie na tumult. Prolegomena do badań nad przemocą w stosunkach międzywyznaniowych w Rzeczypospolitej w XVI i XVII wieku - Hryniewicz, Iwo (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
In this article the nature of religious violence is discussed with particular reference to the work and deeds of a Polish court preacher, Piotr Skarga. The author tries to place the aforementioned phenomenon in a wider cultural context. Drawing from a wide range of sociological and anthropological studies and proposing to understand violence not merely as an act of physical aggression, but also as a process of dehumanizing the enemy and thus making him/her liable to physical harm. The author argues that violence is intrinsic to the world of divided religious communities and can be considered by its perpetrators as an act of piety and doing God’s work. In the Polish context Piotr Skarga was one of the main representatives of this attitude.